Urkunde über den Chieftancy Titel Yeye Olana (‚Mutter der Künstlerinnen und Künstler’) (Of Art Worlds - Collecting and Archiving Modern and Contemporary Art on the African Continent, 1992)
Copyright jointly or exclusively held by Iwalewahaus, CBCIU and/or Georgina Beier Estate Executor. CBCIU and Iwalewahaus identifiers currently unavailable.
Keywords: Ritual; Africa; Women; Women artists; Artists; Archives; Osogbo; Nigeria; Chieftancy; Certificate